NDM-1-Positive K. pneumoniae at a Teaching Hospital in Southwestern China: Clinical Characteristics, Antimicrobial Resistance, Molecular Characterization, Biofilm Assay, and Virulence - Kai Yang; Shumin Liu; Huanqin Li; Na Du; Jing Yao; Qiuyue He; Yan Du (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. The emergence of the NDM-1-positive Klebsiella pneumoniae (K. pneumoniae) strains has led to limited therapeutic options for clinical treatment. Understanding the clinical characteristics, antimicrobial resistance, biofilm assay, and the virulence genes of these isolated strains is of great significance. Methods. The polymerase chain reaction (PCR) was used to screen isolated NDM-1-positive K. pneumoniae. The clinical information of the patients was collected from medical records. The NDM-1-positive K. pneumoniae isolates were subjected to antimicrobial susceptibility testing and multilocus sequence typing. Sixty strains of NDM-1-negative K. pneumoniae isolated during the same period were collected as the control group for the virulence analysis. The virulence phenotype of the strains was preliminarily evaluated by the string test and crystal violet semiquantitative biofilm formation experiment. PCR combined with gene sequencing was used to detect common high toxicity capsule genes (K1, K2, K5, K20, K54, and K57) and common virulence-related genes (entB, ybtS, ureA, ycf, WabG, FimH, uge, iutA, KfuB, aerobactin, rmpA, magA, Alls, IrnN, and VatD). Results. In the 30 nonduplicated NDM-1-positive K. pneumoniae isolates, 43.33% (13/30) of the patients had a history of a stay in the neonatal intensive care unit (NICU). All of the isolates exhibited multidrug resistance. Nine STs were identified, 77% (10/13) strains from the NICU were ST11. The NDM-1-positive K. pneumoniae string tests were all negative, and 35% (21/60) NDM-1-negative K. pneumoniae were positive. The ratios of NDM-1-positive K. pneumoniae isolates biofilm formation ability according to strong, medium, and weak classification were 67%, 23%, and 10%, respectively. NDM-1-negative K. pneumoniae isolates were 60%, 25%, and 15%, respectively. There was no statistical difference between the two groups (t = 0.61, P=0.2723). The virulence-associated genes with more than 80% of detection rates among the 30 NDM-1-positive K. pneumoniae isolates included entB (100%, 30/30), ybtS (93.33%, 28/30), ureA (90%, 27/30), ycf (83.33%, 25/30), and wabG (90%, 27/30). KfuB and iutA were detected at prevalence of 3.33% and 13.33%. vatD, allS, iroN, aerobactin, and rmpA were not detected. In the NDM-1-negative K. pneumoniae, all other 14 virulence genes except VatD were detected. After statistical analysis, FimH, WabG, ycf, iutA, kfuB, aerobactin, rmpA, and Alls virulence genes, P<0.005, there was a statistical difference. Conclusion. NDM-1-positive K. pneumoniae exhibited multidrug resistance, MLST typing is mainly ST11, there is small clonal dissemination in the NICU in the hospital, and the NDM-1-positive K. pneumoniae virulence genes carrier rate is lower than the NDM-1-negative K. pneumoniae virulence genes carrier rate.